Aloperine Ameliorates IMQ-Induced Psoriasis by Attenuating Th17 Differentiation and Facilitating Their Conversion to Treg - Zhou, Hai-Feng; Wang, Fa-Xi; Sun, Fei; Liu, Xin; Rong, Shan-Jie; Luo, Jia-Hui; Yue, Tian-Tian; Xiao, Jun; Yang, Chun-Liang; Lu, Wan-Ying; Luo, Xi; Zhou, Qing; et al. (Frontiers in Pharmacology, 2022)
Aloperine is an anti-inflammatory compound isolated from Chinese herb Sophora alopecuroides L. Previously, our group has reported that the generation of induced Treg was promoted by aloperine treatment in mouse colitis model. However, the effect of aloperine on effector T cell subsets remain unclear. We therefore carefully examined the effect of aloperine on the differentiation of major subsets of T helper cells. Based on our results, psoriasis, which is a Th17 dominant skin disease, is selected to explore the potential therapeutic effect of aloperine in vivo. Herein we demonstrated that topical application of aloperine suppressed epidermal proliferation, erythema and infiltration of inflammatory cells in skin lesions. Mechanistic studies revealed that aloperine suppressed the differentiation of Th17 cells directly through inhibiting phosphorylation of STAT3 or indirectly through impairing the secretion of Th17-promoting cytokines by dendritic cells. Meanwhile, aloperine enhanced the conversion of Th17 into Treg via altering the pSTAT3/pSTAT5 ratio. Collectively, our study supported that aloperine possesses the capacity to affect Th17 differentiation and modulates Th17/Treg balance, thus alleviating imiquimod (IMQ)-induced psoriasis in mouse model.